2020
DOI: 10.3928/1081597x-20200318-01
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcomes and Subjective Experience After Combined Implantation of Extended Depth of Focus and Trifocal IOLs

Abstract: PURPOSE: To evaluate postoperative visual performance and patient-reported outcomes following combined implantation of an extended depth of focus (EDOF) intraocular lens (IOL) and a trifocal IOL. METHODS: The study enrolled consecutive patients undergoing refractive lens extraction or cataract surgery with combined implantation of an EDOF IOL (dominant eye) and a trifocal IOL in the nondominant eye. Uncorrected (UDVA) and corrected (CDVA) distance visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…As found in our previous study [7], there is a hyperopic tendency at both postoperative assessments with the EDOF IOL (Fig. 4), which may be due keratometric changes or to the IOL moving posteriorly due to capsular contractions [18,19], and direct assessment of IOL shift would further help explain the cause.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As found in our previous study [7], there is a hyperopic tendency at both postoperative assessments with the EDOF IOL (Fig. 4), which may be due keratometric changes or to the IOL moving posteriorly due to capsular contractions [18,19], and direct assessment of IOL shift would further help explain the cause.…”
Section: Discussionsupporting
confidence: 67%
“…Various methodologies have been introduced in modern day lens-based surgery to provide a range of clear vision [1][2][3][4][5][6] with the least amount of visual side effects. Our recent study [7] sought to outline the clinical and patient-reported outcomes at an early postoperative period of the latest extended depth of focus (EDOF) technology, thought to provide superior intermediate vision with fewer unwanted visual phenomena, implanted in combination with a trifocal intraocular lens (IOL). The EDOF IOL was used in the dominant eye to provide good distance, intermediate and improve near vision and produce fewer unwanted visual phenomena, with the trifocal IOL implanted in the nondominant eye to provide adequate reading vision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectacle independence at far and intermediate distances was achieved in all patients, while the rate of spectacle independence was just slightly lower at the near distance (96%). Although there was a small number of patients who still needed spectacles for working in the near distance, a very high degree of spectacle independence was achieved with similar outcomes compared to rates in previous studies with the same IOLs [ 27 ].…”
Section: Discussionmentioning
confidence: 72%
“…The binocular defocus curve showed significantly better visual acuity results compared to the AT LISA tri IOL eyes at defocus levels of −1.0 D and −1.5 D ( P =0.008 and P =0.002, respectively) and the AT LARA IOL eyes at defocus levels of −3.0, −3.5 D, and −4.0 D ( P =0.019, P =0.019, and P =0.035, respectively). Richard et al showed a similar defocus curve in patients with combined IOL implantation and also presented better visual acuity results at defocus levels of −1.0 D in patients with bilateral EDoF IOL implantation [ 27 ]. However, there were only 5 patients with bilateral EDoF IOLs, and no other information is available.…”
Section: Discussionmentioning
confidence: 99%